Coordinated Control Strategy Research of Multi-terminal Cascaded Hybrid HVDC System. Issue 1 (February 2021) - Lin, Chang; Zhou, Jiapei; Zeng, Rui; Li, Baohong; Jiang, Qin
Abstract: The multi-terminal cascaded hybrid HVDC system is proposed in recent years and it will be put into reality in near future. This paper investigates its control characteristics when MMCs are in master-slave strategy, and the coordinated control improving system stability is also proposed. It is found that the MMC inverter in constant DC voltage control would become a rectifier when fault happens. To solve such problem, the active power reference is immediately adjusted once the fault occurs, such that the DC side operation and AC side voltage stability can both be improved. Nevertheless, the proposed control strategy can also alleviate the large fluctuations in fault recovery process, so that the system can steadily return to original operation point. The simulation results in PSCAD/EMTDC verify the effectiveness of the proposed coordinated control strategy.